2019
DOI: 10.1186/s12885-018-5129-4
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the glycome after HDAC inhibition impact oncogenic potential in epigenetically plastic SW13 cells

Abstract: BackgroundDefects in the type and degree of cellular glycosylation impact oncogenesis on multiple levels. Although the type of glycosylation is determined by protein sequence encoded by the genome, the extent and modifications of glycosylation depends on the activity of biosynthetic enzymes and recent data suggests that the glycome is also subject to epigenetic regulation. This study focuses on the ability of HDAC inhibition to alter glycosylation and to lead to pro-oncogenic alterations in the glycome as asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…6 C). These findings are consistent with previous research demonstrating that BCL2 is overexpressed during EMT [ 24 , 25 ], and provides insight into previously observed chemotherapeutic resistance in SW13+ cells [ 18 ].
Fig.
…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…6 C). These findings are consistent with previous research demonstrating that BCL2 is overexpressed during EMT [ 24 , 25 ], and provides insight into previously observed chemotherapeutic resistance in SW13+ cells [ 18 ].
Fig.
…”
Section: Resultssupporting
confidence: 92%
“…[ 16 ]. However, while HDAC inhibitors induce toxicity and slow cell growth in some cell types, they can also increase metastatic properties and chemotherapy resistance in others [ 17 , 18 ]. As iron is also critical for tumor cell growth, we examined whether manipulation of intracellular iron availability could improve HDAC inhibitor treatment outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, HDACs are related to repression of genes that encode proteins involved in tumorigenesis, specifically in control of cell growth, differentiation and apoptosis [ 7 ]. The association of HDACs with glycosylation patterns has been reported for cancer indications such as neuroblastoma and adrenocortical carcinoma [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we previously found that DR5 is activated by fucosylation for TRAIL-induced apoptosis using our TRAIL variants [47]. Interestingly, recently a relation between HDAC inhibition and glycosylation pattern was reported which can hint at an explanation for increasing sensitivity of TRAIL receptors in the presence of HDAC inhibitors [48]. In our current study, we investigated the expression of DR4 and DR5 on the cell membrane and our results show significant DR4 but not DR5 expression enhancement on DLD-1 cells, while DR5 but not DR4 expression is increased on WiDr cells.…”
Section: Discussionmentioning
confidence: 90%